Composite lubricant containing porous covalent organic framework as well as preparation method and application of composite lubricant

By combining porous covalent organic frame materials with ionic liquids to prepare composite lubricants, the problem of degradation of traditional lubricants in extreme environments is solved, and more stable lubricating performance and reducing the risk of equipment failure are achieved.

CN119823815APending Publication Date: 2025-04-15TIANJIN UNIV OF TECH & EDUCATION (TEACHER DEV CENT OF CHINA VOCATIONAL TRAINING & GUIDANCE)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510017491.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The performance of traditional friction lubricants deteriorates at high or low temperatures, and their viscosity is affected by temperature and pressure, resulting in unstable lubrication effect, and high investment and maintenance costs. The performance of the electronic control system in extreme environments is affected.

Method used

The porous covalent organic frame material is combined with ionic liquid to prepare composite lubricants, and the porous covalent organic frame material is prepared by ultrasonic chemical reaction or hydrothermal synthesis method, and mixed with 1-butyl-3-methylimidazole thiocyanate, 1-ethyl-3-methylimidazole tetrafluoroborate or 1-butyl-3-methylimidazole hexafluorophosphate plasma liquid.

Benefits of technology

The composite lubricant exhibits more stable lubricating performance at high or low temperatures, with a significant reduction in friction coefficient, a reduced wear volume, and a better friction performance under current conditions, reducing the risk of equipment failure and improving operational safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823815A_ABST
    Figure CN119823815A_ABST
Patent Text Reader

Abstract

The invention discloses a composite lubricant containing a porous covalent organic framework as well as a preparation method and application of the composite lubricant. The composite lubricant comprises a porous covalent organic framework material and an ionic liquid, the ionic liquid is 1-butyl-3-methylimidazolium thiocyanate, 1-ethyl-3-methylimidazolium tetrafluoroborate or 1-butyl-3-methylimidazolium hexafluorophosphate, and the porous covalent organic framework material is a porous covalent organic framework material. According to the invention, a porous covalent organic framework (COF) is added into ionic liquid (ILs) as an additive, the ionic liquid provides an ideal ionic microenvironment or is used as an active substance to endow the organic framework with extra functions such as conductivity, fluidity and dispersibility, and the COF can also improve the corrosivity of the ionic liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricants, and in particular to a composite lubricant containing a porous covalent organic framework, and a preparation method and application thereof. Background Art

[0002] Friction and wear refers to the phenomenon of material surface loss and damage caused by friction during the contact and relative movement of objects. In mechanical movement, friction is the main source of energy loss, resulting in heat and material loss. Wear can affect the function of mechanical parts, shorten equipment life, and increase maintenance costs. Friction lubricants reduce direct contact by forming a protective film between contact surfaces, thereby reducing friction and wear. With the acceleration of industrialization, the demand for friction lubricants is increasing, especially in the fields of automobiles, aviation, heavy machinery, etc. High-quality friction lubricants can significantly reduce the friction coefficient, and the lubricating film formed protects the contact surface, reduces the material wear rate, improves mechanical efficiency, protects the metal surface and prevents oxidation corrosion.

[0003] With the advancement of industrial automation and intelligent manufacturing, equipment has higher and higher requirements for lubrication systems. Electronically controlled friction lubricants have gradually emerged as an emerging field with the development of intelligent technology. Electronically controlled friction lubricants combine advanced sensor technology and control systems, and can automatically adjust the distribution, type and viscosity of lubricants according to real-time data to adapt to different working conditions. It can automatically optimize lubrication under various working conditions, adapt to complex operating environments, and detect abnormalities in a timely manner through real-time monitoring and feedback mechanisms, reducing the risk of equipment failure and improving the safety of operation.

[0004] Because traditional friction lubricants may pollute the environment, their performance at high or low temperatures may be reduced, resulting in lubrication failure, and the viscosity of the lubricant is affected by temperature and pressure changes, which may lead to unstable lubrication effects. At the same time, over time, the lubricant may degrade, affecting its lubrication performance. Although electronically controlled lubrication friction lubricants are superior to traditional lubrication systems, their investment and maintenance costs are high. Electronic control systems require complex design and debugging, and have high technical requirements for operators. At the same time, electronic control systems rely on power supplies, which may affect their performance when power is off or unstable. Under extreme environmental conditions (such as high temperature, humidity, etc.), the performance of electronic control systems may also be affected. Summary of the invention

[0005] In order to solve the deficiencies of the above technical solutions, the object of the present invention is to provide a composite lubricant containing a porous covalent organic framework and a preparation method and application thereof.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] A composite lubricant containing a porous covalent organic framework, the composite lubricant comprising a porous covalent organic framework material and an ionic liquid, wherein the ionic liquid is 1-butyl-3-methylimidazole thiocyanate, 1-ethyl-3-methylimidazole tetrafluoroborate or 1-butyl-3-methylimidazole hexafluorophosphate, and the concentration of the ionic liquid in the composite lubricant is 0.1-2 mg / L.

[0008] In the above technical solution, the porous covalent organic framework material is prepared by the following steps:

[0009] The organic boron compound and the hydrate are added to a solvent and mixed evenly, synthesized by ultrasonic chemical reaction, washed, and then solid-liquid separation is performed. The separated gray-purple solid powder is vacuum dried to obtain a porous covalent organic framework material.

[0010] In the above technical solution, the porous covalent organic framework material is prepared by the following steps:

[0011] The organic boron compound and the hydrate are added to a solvent and mixed evenly, and then added to a reactor for a hydrothermal synthesis reaction. After washing, solid-liquid separation is performed, and the separated gray-purple solid powder is vacuum dried to obtain a porous covalent organic framework material.

[0012] In the above technical solution, the organic boron compound is 1,4-phenylenediboric acid.

[0013] In the above technical solution, the hydrate is 2,3,6,7,10,11-hexahydroxytriphenylene hydrate.

[0014] In the above technical solution, the solvent is a mixture of trimethylbenzene and 1,4-dioxane.

[0015] In the above technical solution, the uniform mixing is performed by magnetic stirring, and the stirring time is 10-15 minutes.

[0016] In the above technical solution, the power of the ultrasound is 200-600W, and the ultrasound time is 60-300 minutes.

[0017] In the above technical solution, the synthesis temperature of the hydrothermal synthesis reaction is 80-120°C and the time is 32-72h.

[0018] In the above technical solution, the washing detergent is tetrahydrofuran.

[0019] In the above technical solution, the solid-liquid separation is performed by a centrifuge at a rotation speed of 8000 rpm for 8-10 minutes.

[0020] In the above technical solution, the vacuum drying temperature is 60-80°C and the time is 6-8h.

[0021] In the above technical solution, the solid-liquid separation adopts a sand core filter device, and the filter paper used is organic and has a pore size of 0.22-0.25 μm.

[0022] Another aspect of the present invention also includes a method for preparing the composite lubricant containing the porous covalent organic framework, which includes the following steps: adding the porous covalent organic framework material to an ionic liquid, mixing them evenly, to obtain a composite lubricant.

[0023] Another aspect of the present invention also includes the use of the composite lubricant in the fields of automobiles, aviation and heavy machinery.

[0024] The advantages and beneficial effects of the present invention are:

[0025] 1. The present invention adopts organic materials, which have more complex molecular structure and plasticity.

[0026] 2. The present invention adds a porous covalent organic framework (COF) as an additive to ionic liquids (ILs). The ionic liquid provides an ideal ionic microenvironment or acts as an active substance to give the organic framework additional functions such as conductivity, fluidity, and dispersibility. COF can also improve the corrosiveness of the ionic liquid.

[0027] 3. The present invention uses a composite lubricant prepared from a porous covalent organic framework and an ionic liquid to conduct friction and wear experiments. During the experiment, the two react with each other to produce new compounds. The composite lubricant has a similar average friction coefficient to that of pure ionic liquids, but the friction coefficient is significantly reduced in the first 400 seconds. In particular, when the addition amount is 0.1wt%, the friction coefficient is reduced from 0.0986 to 0.0769 in the first 600 seconds and remains stable in the subsequent friction. Therefore, the composite lubricant of the present invention can enter the lubrication state faster. The wear volume is reduced from 7.53×10 5 μm 3 Reduced to 4.02×10 5 μm 3 Compared with conventional friction, the average friction coefficient decreased from 0.0756 to 0.0684 under the current condition of 10mA, and the average friction coefficient decreased from 0.0756 to 0.0674 under the current condition of 50mA. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The nitrogen adsorption-desorption curve and average pore size distribution diagram of the porous covalent organic framework material of Example 2;

[0029] Figure 2XRD spectra of the porous covalent organic framework materials of Examples 1 to 3;

[0030] Figure 3 This is a SEM image of the morphology of the porous covalent organic framework material of Example 2;

[0031] Figure 4 This is a SEM image of the morphology of the porous covalent organic framework material of Example 5;

[0032] Figure 5 It is a conventional friction curve diagram of the composite lubricant of Example 7 and 1-butyl-3-methylimidazole thiocyanate;

[0033] Figure 6 It is a conventional wear volume diagram of the composite lubricant of Example 7 and 1-butyl-3-methylimidazole thiocyanate;

[0034] Figure 7 This is the current-carrying friction curve of the composite lubricant of Example 7 at a concentration of 0.1 wt%. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0036] Example 1

[0037] like Figure 1-Figure 4 As shown, a method for preparing a porous covalent organic framework material comprises the following steps:

[0038] Step 1, adding 177 mg of 1,4-phenylenediboronic acid and 242 mg of 2,3,6,7,10,11-hexahydroxytriphenylene hydrate to a solvent, and magnetically stirring for 10 minutes to mix evenly to obtain a mixed solution, wherein the solvent is a mixture of 20 mL of mesitylene and 20 mL of 1,4-dioxane.

[0039] Step 2, subjecting the mixed solution obtained in step 1 to an ultrasonic chemical reaction at an ultrasonic power of 600 W for 1 h to synthesize a mixture.

[0040] Step 3, washing the mixture obtained in step 2 twice with tetrahydrofuran to remove excess impurities, and then placing it in a centrifuge at a speed of 8000 revolutions per minute for 10 minutes to perform solid-liquid separation to obtain a solid powder (gray-purple).

[0041] Step 4, placing the solid powder obtained in step 3 into a vacuum drying oven, and vacuum drying it at 60° C. for 6 hours to obtain a porous covalent organic framework material (porous COF nanomaterial).

[0042] Example 2

[0043] A method for preparing a porous covalent organic framework material. Compared with Example 1, the preparation method of this embodiment has an ultrasonic treatment time of 3 hours, and the remaining steps are the same to obtain a porous covalent organic framework material (porous COF nanomaterial).

[0044] The specific surface area, average pore size and X-ray diffraction of the porous COF nanomaterial obtained in this example were measured, and the morphology was observed by scanning electron microscopy (SEM), showing the nitrogen adsorption and desorption curve ( Figure 1 )、XRD spectrum( Figure 2 )、Topography( Figure 3 ).

[0045] Depend on Figure 1 It can be seen that the N2 adsorption-desorption isotherm of porous COF nanomaterials is a type IV isotherm with a hysteresis loop. In this process, the adsorption process shows that porous COF nanomaterials are similar to mesoporous materials.

[0046] Depend on Figure 3 It can be seen that the average particle size of the porous COF nanomaterial is about 100-400 nm, and the particles of the porous COF nanomaterial present a lamellar structure, showing good dispersion and uniformity.

[0047] Example 3

[0048] A method for preparing a porous covalent organic framework material. Compared with Example 1, the preparation method of this embodiment has an ultrasonic treatment time of 5 hours, and the remaining steps are the same to obtain a porous covalent organic framework material (porous COF nanomaterial).

[0049] Depend on Figure 2 It can be seen that the porous COF nanomaterials of Examples 1 to 3 all show all main peak positions in three different time periods, and the main diffraction peaks

[100] ,

[110] ,

[210] and

[001] are retained. The peak at

[100] of the porous COF nanomaterial of Example 2 is sharper, proving that its crystallinity and purity are higher, and the crystals are more regular.

[0050] Example 4

[0051] A method for preparing a porous covalent organic framework material comprises the following steps:

[0052] Step 1, adding 100 mg of 1,4-phenylenediboronic acid and 64 mg of 2,3,6,7,10,11-hexahydroxytriphenylene hydrate to a solvent, and magnetically stirring for 10 minutes to mix evenly to obtain a mixed solution, wherein the solvent is a mixture of 2 mL of mesitylene and 2 mL of 1,4-dioxane.

[0053] Step 2, placing the mixed solution obtained in step 1 in a reaction kettle containing a polyfluoroethylene liner, and performing a hydrothermal synthesis reaction at 80° C. for 72 hours to obtain a mixture.

[0054] Step 3, washing the mixture obtained in step 2 twice with tetrahydrofuran to remove excess impurities, placing it in a sand core filter device, vacuum filtering, and performing solid-liquid separation to obtain a solid powder (gray purple).

[0055] Step 4, placing the solid powder obtained in step 3 into a vacuum drying oven, and vacuum drying it at 60° C. for 6 hours to obtain a porous covalent organic framework material (porous COF nanomaterial).

[0056] Example 5

[0057] A method for preparing a porous covalent organic framework material. Compared with Example 4, the temperature of the hydrothermal synthesis reaction is 100°C, and the remaining steps are the same to obtain a porous covalent organic framework material (porous COF nanomaterial) such as Figure 4 shown.

[0058] Depend on Figure 4 It can be seen that the porous COF nanomaterial of this embodiment has an obvious lamellar structure and is evenly distributed.

[0059] Example 6

[0060] A method for preparing a porous covalent organic framework material. Compared with Example 4, the temperature of the hydrothermal synthesis reaction in this embodiment is 120° C., and the remaining steps are the same to obtain a porous covalent organic framework material (porous COF nanomaterial).

[0061] Example 7

[0062] A method for preparing a composite lubricant containing a porous covalent organic framework comprises the following steps:

[0063] The porous covalent organic framework material prepared in Example 2 was added to 1-butyl-3-methylimidazole thiocyanate, and the mixture was uniformly mixed by ultrasonication at 600 W for 10 minutes to obtain a composite lubricant.

[0064] Based on the preparation method of this embodiment, the concentrations of the porous covalent organic framework material in the composite lubricant are 0wt%, 0.1wt%, 0.5wt%, 1.0wt% and 2wt%, respectively.

[0065] Conventional friction and wear tests and current-carrying friction and wear tests were performed on the composite lubricants of different concentrations prepared in this example. The results are as follows: Figure 5-Figure 7 shown.

[0066] Depend on Figure 5It can be seen that without adding porous covalent organic framework materials, the average friction coefficient of pure 1-butyl-3-methylimidazole thiocyanate is 0.0732. Compared with pure 1-butyl-3-methylimidazole thiocyanate, the average friction coefficient of the composite lubricant with different concentrations of porous covalent organic framework materials is not much different, but within the first 400s, its friction coefficient is significantly reduced. In particular, when the addition amount is 0.1wt%, the friction coefficient decreases from 0.0986 to 0.0769 within the first 600s and remains stable in the subsequent friction state. Its friction coefficient curve decreases earlier than that of pure 1-butyl-3-methylimidazole thiocyanate, and enters the lubrication state faster.

[0067] Depend on Figure 6 It can be seen that the wear volume after lubrication with pure 1-butyl-3-methylimidazole thiocyanate is 7.526×10 5 μm 3 After adding the porous covalent organic framework material, the wear volume was reduced to a certain extent due to its surface repair effect. The wear volumes at concentrations of 0.1wt%, 0.5wt%, 1.0wt%, and 2wt% were 4.019×10 5 μm 3 4.098×10 5 μm 3 5.489×10 5 μm 3 4.107×10 5 μm 3 The most obvious change was observed when the concentration was 0.1wt%, and the wear volume decreased by 46.64% compared with pure 1-butyl-3-methylimidazole thiocyanate.

[0068] Depend on Figure 7 It can be seen that the current-carrying friction and wear test was carried out on the composite lubricant of Example 7 with a concentration of 0.1wt%, and the applied currents were 10mA, 30mA, and 50mA, respectively, and compared with no current (0mA). When the current size is 10mA, the duration of the friction curve decline (1200s) is longer than that of 30mA (200s) and 50mA (100s). When the current is 30mA, the friction curve rises more violently and fluctuates significantly, so the average friction coefficient (0.0774) when the current of 30mA is applied is significantly higher than that of 10mA (0.0684) and 50mA (0.0674).

[0069] Example 8

[0070] A method for preparing a composite lubricant containing a porous covalent organic framework comprises the following steps:

[0071] The porous covalent organic framework material prepared in Example 2 was added to 1-ethyl-3-methylimidazolium tetrafluoroborate, and the mixture was uniformly mixed by ultrasonication at 600 W for 10 minutes to obtain a composite lubricant.

[0072] Based on the preparation method of this embodiment, the concentrations of the porous covalent organic framework material in the composite lubricant are 0.1 wt %, 0.5 wt %, 1.0 wt % and 2 wt % respectively.

[0073] Example 9

[0074] A method for preparing a composite lubricant containing a porous covalent organic framework comprises the following steps:

[0075] The porous covalent organic framework material prepared in Example 2 was added to 1-butyl-3-methylimidazole hexafluorophosphate, and the mixture was uniformly mixed by ultrasonication at 600 W for 10 minutes to obtain a composite lubricant.

[0076] Based on the preparation method of this embodiment, the concentrations of the porous covalent organic framework material in the composite lubricant are 0.1 wt %, 0.5 wt %, 1.0 wt % and 2 wt % respectively.

[0077] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A composite lubricant containing a porous covalent organic framework, characterized in that: The composite lubricant comprises a porous covalent organic framework material and an ionic liquid, wherein the ionic liquid is 1-butyl-3-methylimidazole thiocyanate, 1-ethyl-3-methylimidazole tetrafluoroborate or 1-butyl-3-methylimidazole hexafluorophosphate, and the concentration of the ionic liquid in the composite lubricant is 0.1-2 mg / L.

2. The composite lubricant according to claim 1, characterized in that: The porous covalent organic framework material is prepared by the following steps: The organic boron compound and the hydrate are added to a solvent and mixed evenly, and then ultrasonic chemical reaction synthesis or hydrothermal synthesis reaction is performed. After washing, solid-liquid separation is performed, and the separated solid powder is vacuum dried to obtain a porous covalent organic framework material.

3. The composite lubricant according to claim 2, characterized in that: The organic boron compound is 1,4-phenylenediboronic acid; the hydrate is 2,3,6,7,10,11-hexahydroxytriphenylene hydrate; and the solvent is a mixture of trimethylol and 1,4-dioxane.

4. The composite lubricant according to claim 2, characterized in that: The uniform mixing is performed by magnetic stirring, and the stirring time is 10-15 minutes.

5. The composite lubricant according to claim 2, characterized in that: The ultrasonic power of the ultrasonic chemical reaction is 200-600W, and the ultrasonic time is 60-300 minutes.

6. The composite lubricant according to claim 2, characterized in that: The synthesis temperature of the hydrothermal synthesis reaction is 80-120° C. and the time is 32-72 hours.

7. The composite lubricant according to claim 2, characterized in that: The solid-liquid separation is performed by a centrifuge at a rotation speed of 8000 rpm for 8-10 minutes.

8. The composite lubricant according to claim 2, characterized in that: The vacuum drying temperature is 60-80°C and the time is 6-8h.

9. The method for preparing a composite lubricant according to any one of claims 1 to 8, characterized in that: The following steps are involved: The porous covalent organic framework material is added into the ionic liquid, and ultrasonically mixed to obtain a composite lubricant.

10. Use of the composite lubricant according to any one of claims 1 to 8 in the fields of automobiles, aviation and heavy machinery.

Citation Information

Cited By

  • Hydrophilic covalent organic framework modified PEEK composite material and preparation method thereof

    CN120289976A